Controversial issues in social studies education in Turkey : the contemporary debates - Gunel, Elvan (Research in social education., 2018)
"Controversial Issues in Social Studies Education in Turkey: The Contemporary Debates consists of different research each analyze a controversial topic that is significant to understand the social and political dynamics of Turkish society and culture. One of the purpose of this volume is to analyze and discuss how various controversial issues are perceived by Turkish educators. It also provides insight about how to think and re-organize education both in Turkey and in a global world by taking perceptions of in-service and pre-service social studies teachers on controversial issues and how to teach about them in the Turkish context into consideration. Lastly, it may provide educators and researchers who are interested in teaching and examining such issues with a holistic view"--